Continuous flow reaction system for the synthesis of 2, 2, 2-trichloroacetophenone derivatives and its application. Issue 11 (14th March 2018) - Ko, Byeng Ha; Yu, Subeen; Song, Kwang Ho; Lee, Sunwoo
Graphical abstract: Highlights: Flow system for the decarboxylative trichlorination of alkynyl carboxylic acid. Synthesis of 2, 2, 2-trichloroacetophenone derivatives. Continuous flow reaction for the synthesis of amide from alkynyl carboxylic acid. Abstract: A continuous flow reaction system was developed for the synthesis of 2, 2, 2-trichloroacetophenone derivatives. When aryl propiolic acids and water were mixed with trichloroisocyanuric acid in DMF at 5 °C, the 2, 2, 2-trichloroacetophenone derivatives were formed within 5 min with good yields. In addition, the resulting mixture was flowed to react with amines to give the corresponding benzamide. This flow reaction system provided higher yields within shorter times than the batch reaction system.